ISLAMIC DIGITAL BANK ADOPTION IN DEVELOPING COUNTRIES: A CASE STUDY ON MILLENNIALS IN INDONESIA - Rumanto, Agep (NISBAH: Jurnal Perbankan Syariah, 2023)
Digital bank is one of the latest cutting-edge on financial technology. This research purpose is to analyze Indonesian millennials behavior toward adoption on digital bank by utilizing extended Technological Acceptance Model (TAM). A partial least square-structural equation model (PLS-SEM) is used to analyze the data of 113 respondents. Based on the findings, the perceived ease of use, perceived usefulness, risk and religiosity determined the intention to adopt Islamic digital bank. In this study also revealed that religiosity insignificant in moderating usefulness toward intention to adopt Islamic digital bank. The research finding extends the TAM with risk and religiosity. These findings contribute extensively to the digital bank literature and theories associated with TAM framework.